ANALISIS RASIO KEUANGAN PERBANKAN TERHADAP KINERJA KEUANGAN DENGAN SUKU BUNGA SEBAGAI MODERASI - Kristanto, Alfred (Jurnal Muara Ilmu Ekonomi dan Bisnis, 2018)
This study to analyze the effect of loan to deposit ratio, operational income operational expense, economic value added, return on asset, and capital adequacy ratio to stock return with interest rate of bank Indonesia as a moderation variable. Population used in this research is listed banking sector issuer in Indonesia Stock Exchange year 2012-2016. Data processing using SPSS version 24.0 testing using moderated regression analysis. Result on the research showed loan to deposit ratio, operational income operational expense, and capital adequacy ratio influence on stock return. Meanwhile, economic value added and return on assets not have influence on stock return. Simultaneously loan to deposit ratio, operational expense of operating income, economic value added, return on asset, and capital adequacy ratio have an effect on stock return.This study was conducted to analyze the effect of loan to deposit ratio, operating income, operating expense, economic value added, return on asset, and capital adequacy ratio on Stock Return with interest rate of Bank of Indonesia as moderating variable. Population used in this research is banking sector issuer listed in Indonesia Stock Exchange year 2012-2016. Data was processed using SPSS version 24.0, while moderated regression analysis was used in testing. Result indicates that loan to deposit ratio, operating income, operating expense, and capital adequacy ratio influence on stock return. Meanwhile, economic value added and return on assets have no effects on stock return. Simultaneously, loan to deposit ratio, operating expense, operating income, economic value added, return onasset, and capital adequacy ratio affect stock return.Keywords : Bank Financial Ratio, Financial Performance, Interest Rate, Stock Return, Deposit Ratio.